Production of Persian Morphosyntactic Structures Based on P-LARSP: Comparing Children With/Without Hearing Loss - Masoomeh Salmani; Sepideh Seyed; Sara Moradi; Zohreh Shirkavand; Sahar Sadati; Maryam Sadat Tabatabaei (University of Social Welfare and Rehabilitation Sciences, 2021)
Objective Despite all advancements in hearing amplification, screening, and interventions, concerns still exist about the language outcomes in children with mild to severe hearing loss. The present study aimed to investigate the production of inflectional morphemes, phrase, and clause structures of children with Moderately Severe Hearing Loss (MSHL) and compare with those of the children with Normal Hearing (NH). Materials & Methods The study participants were 88 NH children, aged 2-5 years, and 10 MSHL children, aged 5-6 years. They were recruited by a convenient sampling method. Speech therapists collected language samples in a free play context of the study children, and then the language samples were transcribed and segmented according to P-LARSP (language assessment, remedy, and screening procedure). Of 100 analyzable units, the speech therapists identified, allocated, and counted 14 inflectional morphemes and all clause and phrase structures in each language sample. Results Children with MSHL used significantly fewer numbers of inflectional morphemes (P=0.004), verb/complement+personal pronoun (P=0.009), and prefix/mi/as a tense marker (P=0.025), lower mean length of morpheme/analyzable utterances (P=0.003), higher percentages of one-word utterances (P=0.001), and lower numbers of clause structures in stage V (P=0.002) compared with NH children aged 4-5 years. While the types of clause structures in children with MSHL were similar to those in NH children aged 24-36 months. However, the types of produced inflectional morphemes were restricted compared with all groups of children with NH. Conclusion The present study revealed that children with MSHL are behind younger children with NH in grammatical aspects of the Persian language. They used simpler clauses, limited numbers, and types of inflectional morphemes, as well as clause and phrase structures, and mainly relied on one-word utterances. Continued monitoring of grammatical outcomes is warranted, considering that children who are MSHL are at increased risk for language problems.